Hydrogeochemistry and Water Quality Assessment in the Thamirabarani River Stretch by Applying Gis and Pca Techniques - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The primary objective of this research is to assess the hydrogeochemical features and water quality of the Thamirabarani river stretch, located in southern India. Thirty-five water samples from the Thamirabarani river stretch were obtained from the districts of Tirunelveli and Thoothukudi. Twelve water quality parameters were measured during the pre-monsoon and post-monsoon periods of 2020 and 2021. The analytical results were verified with BIS and WHO standards to evaluate the water for drinking purposes. A Geographic Information system (GIS) was applied to know the spatial variation of the hydrogeochemical properties over the research area. Moreover, the Water Quality Index was calculated and it was revealed that 15% of the water samples used are outstanding, 35% are fit for potable use, 25% are poor, 15% water are very poor, and 10% unfit for consumption. Principal Component analysis (PCA) was performed to find out the dominant factors and their variance coverage for the overall water quality. The PCA results indicate that a water sample in Zone 1 is known for its alkalinity. The water qualities in Zone 2 and Zone 3 were affected by anthropogenic factors and industry wastes. More sea water intrusion was observed in Zone 4 in the water quality of the Thamirabarani river basin. © 2022 by the authors.